Influence of vermicompost on the growth and yield of cucumber under different growing conditions - Sawaira Ishaq; Faiza Aman (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2025)
A research titled "Influence of vermicompost on the growth and yield of cucumber under different growing conditions" was carried out at the Horticulture Ornamental Nursery, The University of Agriculture Peshawar during summer, 2024. The experiment was laid out using RCBD (Randomized Complete Block Design) with a split plot arrangement having two factors. The first factor included growing conditions (Open field and Shade house with 50% shade), while the second factor comprised levels of vermicompost (0, 1.5, 2.5, and 3.5 tons ha-1). Results showed that both the factors significantly influenced the growth and yield attributes of cucumber. Cucumber plants grown under shade house conditions exhibited superior performance across most attributes compared to those grown under open field conditions. The highest vine length (81.07 cm), number of branches plant-1 (11.68), number of leaves plant-1(31.00), days to 50 % flowering (41.08),number of fruits plant-1(14.03), single fruit weight (237.55 g), fruit diameter (5.40 cm), fruit length(17.15 cm), fruit volume (170.83 cm3) and yield (20.56 tons ha-1) were recorded for those plants which were raised under the growing conditions of shade house. However, plants which were grown under open field conditions showed the lowest vine length (79.93 cm), number of branches plant-1 (8.75), number of leaves plant-1(25.64), days to 50 % flowering (36.46), number of fruits plant-1(12.63), single fruit weight (233.04 g), fruit diameter (5.07 cm), fruit length(16.28 cm), fruit volume (169.20 cm) and yield (19.10 tons ha-1). Similarly, application of vermicompost significantly improved the performance of plants across all parameters. Maximum vine length (84.65cm), number of branches plant-1(14.93), number of leaves plant-1(40.97), days to 50 % flowering (36.85), number of fruits  plant-1 (18.88), single fruit weight (248.7g), fruit diameter (6.65 cm), fruit length(18.68 cm), fruit volume (175.82 cm3) and yield (23.22 tons ha-1), while minimum days to flowering (36.17) were recorded at 3.5 tons ha-1 of vermicompost. The lowest vine length (76.02), number of branches plant-1(6.12), number of leaves plant-1(19.60), days to 50 % flowering(40.75), number of fruits plant-1(8.58), single fruit weight (221.27g), fruit diameter (4.13cm), fruit length (14.97cm), fruit volume (164.25 cm3) and yield (15.05 tons ha-1) were recorded in control plots where no vermicompost was applied. In conclusion, growing conditions of shade house showed positive effects on the growth and yield of cucumber compared to open field conditions during summer. Moreover, vermicompost at the rate of 3.5 tons ha-1 exhibited good effects on the growth and yield of cucumber. Hence, shade house conditions and vermicompost at the rate of 3.5 tons ha-1 are recommended for the better growth and production of cucumber during summer in Peshawar region.